The Rise and Fall of Mexico’s Green Movement - Díez, Jordi (European Review of Latin American and Caribbean Studies, 2008)
An important component of the process of political change Mexico has undergone over the last two decades has been mass mobilization of society, as numerous sectors have pulled out of corporatist structures and placed demands directly upon the state. It is within this ‘thickening’ of civil society that Mexico’s environmental movement emerged, strengthened and was ultimately able to achieve numerous policy triumphs during the 1990s. Puzzlingly, however, since the end of PRI rule in the 2000 elections and the advent of democratic politics, Mexico’s environmental movement has suffered a severe weakening, a weakening which has resulted in very limited impact on national environmental policy. This article examines the reasons behind the weakening of Mexican environmentalism since 2000. Based on data obtained through field research and in-depth personal interviews with key state and non-state actors, this article presents the argument that the weakening of the Mexican environmentalism is primarily due to a ‘leadership vacuum’ produced by the inclusion of the movement’s key actors into positions within the Environment Ministry during the first half of Fox’s administration (2000-06). Resumen: Auge y caída del movimiento verde de MéxicoUn importante componente del proceso de cambio político que ha sufrido México en las últimas dos décadas ha sido la movilización masiva de la sociedad, a medida que numerosos sectores han salido de sus estructuras corporativas para exigir reivindicaciones directamente al estado. Es dentro de este contexto de ‘densificación’ de la sociedad civil que emergió el movimiento ecologista de México, para luego consolidarse y alcanzar finalmente una serie de logros importantes a nivel de política ambiental durante la década de los 90. Sin embargo, y de manera extraña, desde el fin del priato en las elecciones de 2000 y el advenimiento de la democracia electoral en el país, el movimiento ecologista mexicano parece haberse debilitado, lo que ha resultado en una incidencia mu cho menor en la política ambiental del país. Este artículo analiza los factores que explican este fenómeno. Basándose en investigación de campo y una serie de exhaustivas entrevistas personales con actores estatales y no estatales, el artículo defiende la tesis de que el debilitamiento del movimiento ecologista mexicano se debe primordialmente a una falta de liderazgo provocada por el nombramiento de actores claves del movimiento en importantes cargos dentro de la Secretaría de Medio Ambiente durante la primera mitad del gobierno de Fox (2000-2006).